2016
DOI: 10.1111/jpn.12585
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary fibre:starch ratio in shaping caecal archaea revealed in rabbits

Abstract: In rabbits, many studies have investigated the effect of diet, including the fibre intake, on caecal microbiota; however, there are no direct measurements of the influence of diets with different dietary fibre-to-starch ratios and the archaeal community composition in the caecum. We used 16S rDNA sequencing to investigate the impact of different dietary neutral detergent fibre (NDF)-to-starch ratios (1.0-2.3) on the caecal archaeal community in rabbits. The results revealed that the archaeal community from all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Thus, the methanogenic archaea are widely found in the gastrointestinal tract of herbivores and many methanogens have been isolated and identified from different animals (Jin et al, 2017; Wright et al, 2004). However, almost all of the archaea found in the gastrointestinal tract of animals originated from Euryarchaeota (Jin et al, 2017; Zhu et al, 2016). This was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the methanogenic archaea are widely found in the gastrointestinal tract of herbivores and many methanogens have been isolated and identified from different animals (Jin et al, 2017; Wright et al, 2004). However, almost all of the archaea found in the gastrointestinal tract of animals originated from Euryarchaeota (Jin et al, 2017; Zhu et al, 2016). This was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Venn diagrams, PCA, and heat map plots of the bacterial communities derived from rabbit cecum showed that a shift of dietary fiber can lead to quick changes in the composition of the microbiota, which is a reflection of a rapid adaptation to reach a new equilibrium in response to a nutritional disturbance (Michelland et al., ; Zhu, Sun, Wang, & Li, ). Meanwhile, we found that in the cecum, the structure of the bacterial community has no difference between rabbits of the same age or fed the same diet treatment (Michelland et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the diversity of methanogens decreased with the decrease in alfalfa meal particle size and Witzig et al [ 53 ] reported that ruminant microbial community structure changed according to feed particle size. However, Zhu et al [ 17 ] reported no significant differences in the diversity and abundance of caecal archaeal community of rabbits that were fed diets with different dietary fibre-to-starch ratios.…”
Section: Discussionmentioning
confidence: 99%
“…have been highlighted [ 14 15 ]. Although many studies involve cecal fermentation, the study of methane production by rabbit is limited [ 16 17 ]. Several previous investigations mainly conducted were in vitro experiments [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%